2016
DOI: 10.21859/ijpn-04056
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stressors and Coping Strategies Employed by Retired Elderly

Abstract: Introduction: Elderly when faced with different types of stressors, employ various coping strategies that are associated with different consequences for their physical and mental health. This study aimed to identify the stressors and coping strategies were employed in Elderly of East of Guilan. Methods: This study was cross-sectional correlational-analytic. In this study, 124 elderly over 60 years old randomly selected from East Guilan's Retirement Centers and their demographic factors, stressors in elderly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…If we fail to do so, all efforts regarding lengthening human beings' lifetime will confront devastating consequences [10]. Based on recent studies, the most important factor effecting the health state of the elderly, is stress and anxiety [11][12][13][14][15][16][17][18][19]. on the other hand stress is one of the most important risk factor that due to cancer [20][21][22][23][24][25][26][27][28].…”
Section: Presenting Approaches To Stress Management In the Elderly Inmentioning
confidence: 99%
“…If we fail to do so, all efforts regarding lengthening human beings' lifetime will confront devastating consequences [10]. Based on recent studies, the most important factor effecting the health state of the elderly, is stress and anxiety [11][12][13][14][15][16][17][18][19]. on the other hand stress is one of the most important risk factor that due to cancer [20][21][22][23][24][25][26][27][28].…”
Section: Presenting Approaches To Stress Management In the Elderly Inmentioning
confidence: 99%
“…Abuse is one of the main causes of physical injuries, diseases and reduced quality of life in the elderly (Mohebbi et al, 2016). In cases of continued abuse, in addition to the increased risk of death, the abuse also impacts Given their role in the community, their relationship with all social groups, and their vital role in breaking the cycle of abuse in the lives of the elderly and, consequently, preventing its extensive complications at the level of community, and understanding the meaning of loneliness from the elderly's perspective, this knowledge can increase nurses' ability to investigate, prevent, and intervene in regard with this phenomenon (Gheibizadeh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…7 Various factors such as fear of illness recurrence, body dysmorphic disorder, chemotherapy, surgery, young age, higher degree of illness, and lack of social support can lead to psychological responses in breast cancer patients. 8,9 Psychological responses such as stress, depression, and anxiety are all associated with the disease diagnosis and treatment. 10 Studies have shown the variable prevalence of depression (from 9% to 66%), stress (14.3%), anxiety (from 17.9% to 33%), and psychological disorders (from 15% to 60%) in women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%